A near-infrared fluorescence probe for the detection of bisulfite in vivo and food samples. (April 2022) - Shang, Zhuye; Liu, Jianhua; Hu, Zhizhi; Meng, Qingtao; Wang, Yue; Zhang, Run; Zhang, Zhiqiang
Abstract: The evaluation of the HSO3 − levels in the biological systems and food samples is of great significance in the understanding its physiological/pathological roles and realizing food security supervision. In this work, a near-infrared (NIR) emitted fluorescence probe (QNP ) has been successfully developed to detect HSO3 − in live animals and food samples. QNP was designed with a large π-conjugation structure by conjugating of quinolinium with 3H-naphtho[2, 1-b]pyran moiety through a reactive C=C double bond. Spectroscopic titration, high resolution mass spectrometry (HR MS), 1 H NMR titration and theoretical computation indicates that HSO3 − attacks to the C=C double bond through an established 1, 4-nucleophilic addition reaction leads to the interruption of the π-conjugation system of QNP, resulting in dramatic decline of the UV–vis absorption and fluorescence spectra. QNP was featured with near infrared emission (centered at 690 nm), high water-solubility (98% water), large Stokes shift (218 nm), perfect selectivity, fast response time (within 50 s) to HSO3 −, reliability in broad pH range (6.5–11.5) and low cytotoxicity. The application of QNP in biological systems has been demonstrated by the monitoring of exogenous HSO3 − in live adult zebrafish and nude mouse. Furthermore, the evaluation of HSO3 − level in several food samples including sugar, white wine, canned fruits and jasmine tea drinks were also determined by fluorescence colorimetric method using QNP . Graphical abstract: A near-infrared (NIR) fluorescence probe (QNP ) has been successfully designed with a reactive C=C double bond. Studies indicated that HSO3 − reacts with C=C double bond through the nucleophilic addition reaction, resulting in dramatic decline of the UV–vis absorption and fluorescence spectra. The applications of QNP were successfully demonstrated by the imaging of HSO3 − intake in live animals and the semi-quantitative analysis of HSO3 − in several food samples. Image 1 Highlights: The fluorescence probe (QNP ) was featured with near-infrared emission, high water-solubility and large Stokes shift. QNP specifically responses to HSO3 − with perfect selectivity, fast response time and reliability in broad pH range. The fluorescent imaging function of QNP for HSO3 − tracking in live animals has been successfully realized. Semi-quantitative analysis of HSO3 − levels in four food samples has been realized by "naked-eye" using QNP.